2013 IEEE Conference on Computational Intelligence for Financial Engineering &Amp; Economics (CIFEr) 2013
DOI: 10.1109/cifer.2013.6611689
|View full text |Cite
|
Sign up to set email alerts
|

Price variation limits and financial market bubbles: Artificial market simulations with agents' learning process

Abstract: Financial exchanges sometimes employ a "price variation limit", which restrict trades out of certain price ranges within certain time spans to avoid sudden large price fluctuations.We built an artificial market model implementing a learning process to replicate bubbles that has the continues double auction mechanism and investigated price variation limits. We surveyed an adequate limitation price range and an adequate limitation time span for the price variation limit and found a parameters' condition of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Mizuta et al [12] added a learning process to the model of Chiarella et al [13] and showed that the learning process is needed to replicate dynamic large fluctuations unstably existing in the short term, such as those caused by large erroneous orders. In this study, we additionally implemented a large-erroneous-order process and some order price regulations to the model of Mizuta et al [12].…”
Section: Artificial Market Modelmentioning
confidence: 98%
See 4 more Smart Citations
“…Mizuta et al [12] added a learning process to the model of Chiarella et al [13] and showed that the learning process is needed to replicate dynamic large fluctuations unstably existing in the short term, such as those caused by large erroneous orders. In this study, we additionally implemented a large-erroneous-order process and some order price regulations to the model of Mizuta et al [12].…”
Section: Artificial Market Modelmentioning
confidence: 98%
“…The model of Mizuta et al [12], on which we base our model, was itself based on the model of Chiarella et al [13], which succeed in replicating stylized facts that are the statistical nature of returns stably existing over the long term in almost all financial markets. Mizuta et al [12] added a learning process to the model of Chiarella et al [13] and showed that the learning process is needed to replicate dynamic large fluctuations unstably existing in the short term, such as those caused by large erroneous orders.…”
Section: Artificial Market Modelmentioning
confidence: 99%
See 3 more Smart Citations